Investigating outputs from university-industry-government collaborations in the Technology Station Clothing and Textiles of the Western Cape, South Africa - Mbatha, Sipho (University of Pretoria, 2024)
Dissertation (MConsumer Science (Clothing Management))--University of Pretoria, 2023.